Evaluation of the antigenotoxicity of polysaccharides and beta-glucans from Agaricus blazei, a model study with the single cell gel electrophoresis/Hep G2 assay - Friedmann Angeli, Jose Pedro; Ribeiro, Lúcia Regina [UNESP]; Camelini, Carla M.; de Mendonca, Margarida M.; Mantovani, Mario Sergio (Academic Press Inc. Elsevier B.V., 2009)
The mushroom Agaricus blazei (Agaricus brasiliensis) has been drawing attention because of its medicinal properties. Among its isolated compounds, special consideration is given to beta-glucans, which are cell wall polysaccharides. The aim of the present work was to determine the genotoxic and/or antigenotoxic effects of the total polysaccharides of this mushroom and beta-glucans, both extracted at different stages of fruiting body maturity (immature. mature stage with immature spores and mature stage with mature spores). beta-glucan genotoxicity was examined using the comet assay in the HepG2 cell line. Additionally, the protective effect of total polysaccharides and beta-glucans was tested against H(2)O(2), bleomycin and doxorubicin. The results demonstrated that total polysaccharides and beta-glucans had no genotoxic effects. on the contrary, they protected DNA against damage caused by the three inducers used. However, total polysaccharides had limited protective effects while being ineffective against doxorubicin. Interestingly, the largest protective effect was seen with extracts from the ripest stages and in the absence of isolated beta-glucan. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Agaricus blazei; Mushroom; beta-glucan; Comet assay; Genotoxicity; Antigenotoxicity; HepG2 cell; Bleomycin; Doxorubicin; Food analysis; Food composition